1999
DOI: 10.1007/s002449900476
|View full text |Cite
|
Sign up to set email alerts
|

Yolk PCB and Plasma Retinol Concentrations in Shag ( Phalacrocorax aristotelis ) Hatchlings

Abstract: To evaluate the possibilities of applying plasma retinol as a biomarker of response in seabirds exposed to chronic low levels of organochlorines, the relationship between yolk content of polychlorinated biphenyls (PCBs) and plasma retinol levels were studied in newly hatched shag chicks (Phalacrocorax aristotelis) from the coast of central Norway. The mean concentration of 29 PCB-congeners (SigmaPCB) in the yolk sac was 1.22 microgram/g ww (wet weight basis) (SD = 0.57, n = 10), or 17.99 ng/g lw (lipid weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…A decrease in T3 and T4 was observed after treatment of chicken embryos with Aroclor 1242 and Aroclor 1254, but not after treatment with PCB congeners # 54, 77 and 80 (Gould et al, 1999). As reported by many authors, various mechanisms, sometimes contradictory, control the levels of retinol and thyroid hormones and contaminants such as PCBs, PCDDs and organochlorines may interfere in many ways in these processes (Brouwer and Van den Berg, 1986;Brouwer et al, 1990;Peakall, 1992;Fairbrother, 1993;Murvoll et al, 1999). Other non-measured contaminants such as coplanar PCB congeners and PCB metabolites may also interfere with the regulation of these systems.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A decrease in T3 and T4 was observed after treatment of chicken embryos with Aroclor 1242 and Aroclor 1254, but not after treatment with PCB congeners # 54, 77 and 80 (Gould et al, 1999). As reported by many authors, various mechanisms, sometimes contradictory, control the levels of retinol and thyroid hormones and contaminants such as PCBs, PCDDs and organochlorines may interfere in many ways in these processes (Brouwer and Van den Berg, 1986;Brouwer et al, 1990;Peakall, 1992;Fairbrother, 1993;Murvoll et al, 1999). Other non-measured contaminants such as coplanar PCB congeners and PCB metabolites may also interfere with the regulation of these systems.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies on effects of dioxin-like contaminants in plasma retinol levels have shown contradictory results (Spear and Bourbonnais, 2000). Murvoll et al (1999) found a borderline significant positive correlation between PCBs in lipid weight and plasma retinol in shag (Phalacrocorax aristotelis) hatchlings, at PCB levels lower than levels in the great blue heron from the St. Lawrence. Murk et al (1994) found increased plasma retinol levels with increasing PCB burden in common tern (Sterna hirundo) hatchlings, while Elliott et al (1996) found no difference in 1-day-old bald eagle chick's plasma retinol among colonies with various levels of dioxin and furan contamination.…”
Section: Discussionmentioning
confidence: 92%
“…Lipid content and mass of yolk sacs in these ospreys also correlated with egg volume and hatchling mass. Murvoll et al [39] reported that lipid content of yolk sac regressed significantly with egg volume and hatchling weight and therefore PCBs and body weight in Norwegian shags ( Phalacrocorax aristotelis ). They argued that their results and a number of the previously reported relationships between embryonic body weight and contaminants were the result of covariation between body weight and lipid content rather than being cause and effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why we found only weak positive relationships for a few contaminants, e.g., TEQs and some PCB congeners, with egg volume and yolk‐free body weight. However, the studies of Custer et al [31] and Murvoll et al [39] focused on single colonies, whereas we collected from seven widely separated sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation